2014
DOI: 10.1002/tox.22019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental safety level of lead (Pb) pertaining to toxic effects on grey mullet (Mugil cephalus) and Tiger perch (Terapon jarbua)

Abstract: Acute and chronic bioassay toxicity test of Lead (Pb) in Grey Mullet (Mugil cephalus), and Tiger perch (Terapon jarbua) was conducted. LC50 values (Lethal Concentration) from acute tests and chronic values were calculated by the geometric mean of the No-Observed-Effect Concentration (NOEC) and the Lowest-Observed-Effect Concentration (LOEC) in a study period of 30 days. This research was conducted to evaluate the quantitative relationship between toxicity test statistics and correlation between toxicant and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In laboratory toxicity tests, GSH/GSSH in gills and in whole fish (including M . cephalus ) increased following Pb exposures [69], while GSH/GSSG levels varied with tissue and life stage following Cd exposure [109, 110]. Specifically, results from the latter two studies indicate GSH/GSSG is biphasic, with increasing activity occurring up until a certain concentration after which levels decline [109, 110].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In laboratory toxicity tests, GSH/GSSH in gills and in whole fish (including M . cephalus ) increased following Pb exposures [69], while GSH/GSSG levels varied with tissue and life stage following Cd exposure [109, 110]. Specifically, results from the latter two studies indicate GSH/GSSG is biphasic, with increasing activity occurring up until a certain concentration after which levels decline [109, 110].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to field studies the responses to Cu and to Cd, respectively, varied with tissue type and showed a biphasic response meaning it could not be used to confirm exposure to higher metal concentrations [109, 110, 116]. In contrast, Pb exposure resulted in a negative response in GST levels in gills and whole juveniles of two different fish species under all concentrations [69]. The absence of a biphasic response to Pb may be due to the metal concentrations not reaching threshold levels for this protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations